Knowledge on nutrition and frequency of food intake among pregnant women visiting Peringgit Community Polyclinic Melaka (PCPM) - Hasan, Haliza (2011)
Introduction: Adequate maternal nutrient intake during pregnancy is essential to ensure satisfactory birth outcomes and prevent adverse effect. Inadequate intake of iron in pregnancy can cause anemia which increases risk of maternal mortality. Hence, a diet rich in iron should be included as an important health education planning on nutrition for pregnant women.